Comprehensive Overview of Preterm Developmental Supportive Care: Narrative Review - Abdul Hussein, Hasan Saud; Shawq, Adraa Hussein (International Journal of Child Health and Nutrition, 2025)
Background: Preterm infants face significant health challenges due to the underdevelopment of their organ systems. The neonatal intensive care unit (NICU) is considered a stressful environment, which can disrupt self-regulation and maturation. Developmental supportive care strategies have been shown to enhance neurodevelopmental outcomes in neonates by mimicking intrauterine conditions, reducing stress, and providing appropriate sensory stimulation. Nursing interventions, particularly developmental care, are essential in improving neonatal health, with nurses playing a pivotal role in implementing these strategies. Aim: This article aimed to provide a comprehensive narrative synthesis of recent research on the impact of developmental supportive care on the health outcomes of preterm infants. Methods: An extensive literature search was conducted across PubMed, Scopus, Web of Science, Google Scholar, and the Cochrane Library. Quantitative studies, quasi-experimental research, observational studies, and meta-analyses of randomized clinical trials published in English within the past decade were included, with a particular emphasis on studies from the last five years. Results: The findings indicated that the application of developmental supportive care strategies in the neonatal intensive care unit significantly improved health outcomes for preterm infants, as reported in previous studies. Conclusion: This narrative overview demonstrated that developmental supportive care effectively contributes to the management and enhancement of preterm infants’ health. The study recommends promoting and standardizing these practices in neonatal intensive care units, conducting a collective review of developmental supportive care techniques, and establishing training programs to improve health outcomes for preterm infants and identify effective interventions.